Improving 11th-Grade Students’ Conceptual Understanding Of The Human Circulatory System Topic Using Multiple Representations In SMA Negeri 8 Makassar - Wesra, Nur Khilal; Palennari, Muhiddin; L, Hamka; Faisal, Faisal (Universitas Negeri Makassar, 2025)
Abstract. This study aims to enhance students’ conceptual understandings of the circulatory system topic by utilizing multiple representations. The method used is Classroom Action Research (CAR), with two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were students in grade 11-Merdeka 6 at SMA Negeri 8 Makassar. The results showed that using multiple representations (macro, micro, sub-micro, and symbolic) significantly increased student understanding of the structure and function of the human circulatory system. The students’ score average increased from 63 in cycle-1 to 77 in cycle-2, with classical mastery increasing from 3.45% to 89.66%. The average N-Gain score of 0.375 falls into the moderate category. This study implies that the multiple representations strategy is effective in deepening students' understanding of abstract biological concepts.Keywords: multiple representations, knowledge of the circulatory system, action research.